Pattern of antibiotic resistance of various strains of bacteria causing acute tonsillitis - Jyothsna, N.; Ramya, A.; Reddy, Kotti Abhilash; Johnson, Bathsa Liza; Bospali, Kavya Sree; G., Ramu; Vyshnavi A., Sree (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Our study was done to determine the pattern of antibiotic resistance of various strains of bacteria causing acute tonsillitis. Methods: the study was a randomized cross sectional study. Patients matching the inclusion criteria were included. Duration of study was 6 months. Results: Out of 120 cases, 46 cases showed no bacterial growth (NBG) and 74 cases showed bacterial growth. 42 cases were gram-negative bacterial strain and 32 cases were positive bacterial strain out of 72 bacterial grown cases. A list of 25 antibiotic drugs in gram-negative and 31 drugs in gram-positive strain, their sensitivity and resistance were taken and noted. Among gram-negative bacteria imipenem (71.4%) showed highest sensitivity. Highest antibiotic resistance was seen in ampicillin (85.71%). Least sensitivity is observed in clindamycin, amoxicillin+clavulanic acid with 2.38%. Among gram-positive bacteria, highest sensitivity was noted in cefotaxime (75%). Highest antibiotic resistance was seen in cotrimoxazole (46.8%). Least sensitivity is observed in netilmicin, sulbactam with 3.12%. Conclusions: The number of drugs resistant to the gram-positive bacteria are lesser than number of drugs sensitive, which showed significant difference (p<0.05). Significant difference of antibiotic drugs was not found in gram-negative bacteria. Our study findings helped in appropriate and guarded use of the antibiotic drugs in acute tonsillitis, minimizing the exposure of individuals to antibiotic resistance by choosing an appropriate sensitive drug, therefore improving the quality of therapy.